Online Group PK Experiments: Hypothesis Testing and Theory Development - McClenon, James (Journal of Scientific Exploration, 2024)
The author conducted weekly online group psychokinesis (PK) experiments between Aug. 9, 2019 and Feb. 25, 2023, with the goal of experiencing collective PK. Participant observation experiments were designed to uncover variables associated with group PK experiences rather than prove the existence of PK. Early experiments seemed to increase individual propensity for spontaneous anomalous experience. The group began attempting to influence pinwheel turning on June 12, 2020. Direct observation seemed to reduce pinwheel turning. Certain conversational elements, such as emotion and discussion of psychical research, seemed to enhance turning. A motion-activated Blink camera was incorporated into the protocol on November 8, 2021, allowing documentation of 44 pinwheel experiments. Experiences involved ostensible anomalous pinwheel turning, equipment failures, poltergeist-like events, and trickster effects. Quantitative results included: (1) Significantly more pinwheel turning, as measured by camera activations, during group meetings compared to equivalent non-group periods; (2) Certain discussion topics were associated with rapid turning: occult traditions, psychic readings, psychical research; and (3) Other variables were associated with reduced turning: direct observation, relaxation exercise, miscellaneous discussion topics. Participants felt that the pinwheels exhibited a form of intelligence due to the pinwheel response to group discussion. Trickster effects included turning patterns that changed over time, unusual equipment failures, and ‘hiding’ behavior thwarting full verification. These features suggest that the replicability of findings may be limited, although a series of methodological guidelines are suggested to increase success. Grounded theory strategies allow theory development, and a new model is proposed to account for the phenomena in question.